Calculators & Converters

    7/10 plus 6/9 as a fraction

    Fraction Addition Calculator

    7/10 + 6/9 as a fraction provides the detailed information about what is 7/10 plus 6/9 in fraction and decimal form, and the answer with steps to understand how it is being calculated by using different methods.

    7/10+6/9 equals to
    7/10 + 6/9 = (?)
    7/10 + 6/9 = [(7 x 9) + (6 x 10)]/(10 x 9)
    = (63 + 60)/90
    = 123/90
    = (3 x 41)/(3 x 30)
    = 41/30
    7/10 + 6/9 = 41/30
    7/10 plus 6/9 is equal to 41/30

    where
    7/10 is a fraction as an addend,
    6/9 is a fraction as an addend,
    41/30 is the sum of 7/10 and 6/9.

    7/10 plus 6/9 as a decimal
    7/10 + 6/9 = 41/30
    41/30 = 1.3667
    7/10+6/9 as a decimal is 1.3667
    where
    1.3667 is the sum of 7/10 and 6/9.

    For values other than 7/10 plus 6/9, use this below tool:

    How-to: 7/10 + 6/9 = ?

    The below workout with step by step calculation shows how to find what is 7/10 plus 6/9 in simplest form by using the following methods:
    1. LCM method,
    2. Cross multiplication method.

    Problem and Workout - LCM Method:
    What is 7/10 plus 6/9 as a fraction?

    step 1 Observe the input parameters and what to be found:
    Input:
    Fraction A: 7/10
    Fraction B: 6/9

    What to be found?
    7/10+6/9 = ?
    Find what's the sum of 7/10 and 6/9.


    step 2 Compare the denominators of fractions 7/10 and 6/9 to identify whether it is a like or unlike fraction addition. Since the denominators of given fractions 7/10 and 6/9 are not equal, it is said to be unlike fractions addition.

    step 3For unlike fractions addition, find the LCM (least common multiple) of both denominators of fractions 7/10 and 6/9:
    The LCM of 10 and 9 is 90.


    step 4 Write the fractions 7/10 and 6/9 in the addition expression form and multiply LCM with all the numerators and denominators of both fractions.
    =7/10+6/9
    =(7 x 90)/(10 x 90)+(6 x 90)/(9 x 90)


    step 5 Simplify the expression to have common denominator:
    =63/90+60/90


    step 6 Take the common values out and rewrite the above expression like the below:
    =1/90 x (63/1+60/1)
    =1/90 x (63 + 60)


    step 7Simplify the above expression further:
    =1/90 x 123
    = 123/90
    =41/30
    7/10+6/9=41/30

    Hence,
    7/10 plus 6/9 equals to 41/30 in fraction.



    Problem and Workout - Cross Multiplication Method
    step 1 Observe the input parameters and what to be found:
    Input:
    Fraction A: 7/10
    Fraction B: 6/9

    What to be found?
    7/10+6/9 = ?
    Find what's the sum of 7/10 and 6/9.

    step 2 Find the product of numerator of Fraction A and denominator of Fraction B (7 x 9), find the product of numerator of Fraction B and denominator of Fraction A (6 x 10), and find the product of both denominators of Fraction A and Fraction B (10 x 9) and rewrite the equation as like the below:
    = (7 x 9) + (6 x 10)/(10 x 9)

    step 3 Simplify and rewrite the fraction:
    = (63 + 60)/90
    = 123/90
    = 41/30
    7/10+6/9 = 41/30
    Hence,
    7/10 plus 6/9 = 41/30

    getcalc.com Calculators